IMPLEMENTASI EDUKASI DIET RENDAH GARAM PADA KELUARGA “NY. R” DENGAN HIPERTENSI DI WILAYAH TODDOPULI 4 RW 5 PUSKESMAS TAMAMAUNG - Stanislaus Kolis Ndawang; Hamsiah Hamzah; Nofianti Nofianti; Hidayanti Ismail (Tasikmalaya Nursing Journal, 2026)
ABSTRAK PENERAPAN EDUKASI DIET RENDAH GARAM PADA KELUARGA PENDERITA HIPERTENSI “NYM. R” DI KECAMATAN TODDOPULI 4 RW 5 WILAYAH KERJA PUSKESMAS TAMAMAUNG STANIS LAUS KOLIS NDAWANG : Mahasiswa Program Studi Diploma 3 Keperawatan Stikes Panaakkukang Makassar Pembimbing : Hamsiah Hamzah dan Nofianti Background: Hypertension is one of the major non-communicable diseases and a leading cause of death globally. Low-salt diet education is a proven non-pharmacological approach to controlling blood pressure. Objektive: This research employed a case study design with a descriptive- narrative approach. The subject was Mrs. R, 54 -year-old hypertensive patient living in the working area of tamamaung public health center. The intervention lasted for three consecutive days using educational materials such as leaflets, posters, and SOP. Data were collected through observation, interviews, questionnaires, and blood pressure measurements. Results: The respondent’s knowledge improved after the intervention (questionnaire score increased from 13 to 18 correct answers ). Blood pressure decreased from 140/100 mmHg to 135/90 mmHg.Conclusion: Systematic and structured low-salt diet education was effective in enhacing knowledge and reducing blood pressure in the hypertensive patient.Recommendation: Nurses should continue providing consistent education. Patients and their families are encouraged to maintain a low-salt diet daily. Future research should consider a longer duration and more interactive educational methods. Keywords: Diet Education Low-Salt, Hypertension. References: 5 Books, 29 Journals.